Assessment of cooperative antibiotic resistance of Salmonella Typhimurium within heterogeneous population. (August 2021) - Dawan, Jirapat; Ahn, Juhee
Abstract: This study was designed to investigate the cooperative resistance in the mixed culture of antibiotic-sensitive and antibiotic-resistant Salmonella Typhimurium. Strains of S . Typhimurium ATCC 19585 (ST S ) and clinically isolated antibiotic-resistant S . Typhimurium CCARM 8009 (ST R ) grown in single and mixture with 1 × MIC ceftriaxone (CEF) were used to determine the viability, β-lactamase activity, and gene expression. The MIC50 values of ST R to CEF was increased by more than 5-fold with increasing inoculum densities from 10 2 to 10 7  CFU/mL. ST S was resistant to 1 × MIC CEF in the mixed culture of ST S and ST R, showing the more than 10 8  CFU/mL after 20 h of incubation at 37 °C. The highest β-lactamase activity was 18 μmol/min/mL in the mixed culture, corresponding to the highest relative expression of β-lactamase-related genes ( bla TEM ). These results shed new light on the cooperative resistance of antibiotic-sensitive bacteria within a heterogeneous population including β-lactamase-producing bacteria. Highlights: The antibiotics susceptibility of Salmonella was decreased with increasing inoculum density. The β-lactamase-producing Salmonella affected the survival of antibiotic-sensitive Salmonella. Antibiotic-sensitive Salmonella exerted the cooperative resistance in heterogeneous population.